Imaging appearances of giant cell tumor of the bone - Ravikanth, Reddy (Med J Armed Forces India, 2021)
Giant cell tumor (GCT) of bone is a benign, locally aggressive lytic lesion in the subarticular location occurring in skeletally mature individuals. Acute hemarthrosis from pathological fracture of GCT should be considered in the differential diagnosis for acute swelling of the knee. Here we describe the imaging appearances of GCT on conventional radiography and magnetic resonance imaging (MRI).